ENHANCING STUDENTS’ KNOWLEDGE ABOUT SEXUAL VIOLENCE PREVENTION IN THE CAMPUS ENVIRONMENT - Anggraini, Rista Dian; Hidayah, Ardiyanti; Farida, Siti Nur (Journal of Indonesian Public Health Service, 2025)
The issue of sexual violence is currently widespread within community environments, including those that should be safe for learning, such as elementary schools and higher education institutions. Sexual violence in educational settings, especially in universities, causes numerous negative impacts on both the physical and mental health of the victims, which can subsequently disrupt the teaching and learning process. One of the preventive measures against sexual violence on campus is through public discussions or socialization activities aimed at students. This community service method is carried out through socialization to enhance students' knowledge about the prevention of sexual violence. This article discusses the importance of increasing students' awareness about preventing sexual violence through socialization activities. These activities serve as a means to raise awareness, provide education, and encourage active participation from all members of the academic community in efforts to prevent sexual violence on campus. Furthermore, socialization can also be used to formulate effective policies and prevention strategies and to build cooperation with various related parties. Thus, through public discussion activities, campuses can foster a safer and more inclusive culture and reduce the incidence of sexual violence.